Information Systems on Learning & Communication Devices for Parents: Media for Learning Acquisition in the Digital Age - Rohita Rohita; Nila Fitria; Dody Haryadi (Research Synergy Foundation, 2022)
During the pandemic, learning for early childhood is carried out in the form of distance learning, both with online and offline models. As a result of this policy, parents in Indonesia must assist their children while studying from home. Various information is needed so that parents can carry out their duties which are at the same time their obligations, in a good and correct way, in accordance with the principles of early childhood learning. Information system for learning and communication devices for parents or abbreviated SIPPKOM, is here to meet the needs of parents to get information about learning needed to help children while learning from home. SIPPKOM is made by utilizing a website to be accessed using a mobile phone or laptop wherever parents are. The purpose of this research is to describe the possible strategies used by parents to obtain information on the core-basic competencies, learn themes, tools, weekly and daily lesson plans, children's progress reports, as well as communicate with teachers through the use of SIPPKOM. This is qualitative research with data collected through observations, interviews, and documentation. The research subjects were 10 parents from 2 partner institutions using SIPPKOM who were willing to be involved in the research. The data collected were analyzed using the Miles and Huberman model with reduction, presentation, and concluding stages. The result showed that parents could easily get information on learning tools, including weekly and daily lesson plans, academic calendars, and E-reports, irrespective of the time and place. Access to SIPPKOM can also be carried out using a cellphone/ smartphone or a laptop. Furthermore, parents can also communicate with teachers without worrying that subsequent ones will overwrite the information provided. The implication of the results of this study is that institutions can provide other communication platforms that can be used to convey information related to learning planning and the abilities achieved by children as a result of their assessment.